Atmospheric corrosion of low carbon steel in a coastal zone of Ecuador: Anomalous behavior of chloride deposition versus distance from the sea. Issue 3 (8th October 2018) - Guerra, Juan C.; Castañeda, Abel; Corvo, Francisco; Howland, Juan J.; Rodríguez, Joelis
Abstract : Atmospheric corrosion of low carbon steel exposed in a coastal tropical zone of Manabí, Ecuador, was determined. Specimens were exposed at six outdoor exposure sites located at different distances from the sea. The atmosphere is classified as coastal. Wind speed threshold for an increase in chloride deposition rate was determined. The behavior of chloride deposition rate versus distance from the sea is anomalous due to the presence of an estuary. Corrosion by weight loss was evaluated up to 1 year of exposure. Only a slight difference in atmospheric corrosion rate is noticed between wet and dry periods. Chloride deposition interaction with RH–temperature complex and with wind speed shows significant statistical influence on atmospheric corrosion of low carbon steel. Corrosivity category of the atmosphere high (C4) is the most predominant classification level in the zone. Prediction indicates corrosivity category high (C4) will remain up to 20 years of exposure. Different morphologies of corrosion products were identified by SEM. Lepidocrocite, goethite, magnetite, and akaganeite are the main crystalline phases determined by XRD. Protective ability index previously proposed for rust layers is not useful to apply in coastal sites. Abstract : Atmospheric corrosion of low carbon steel exposed in a coastal tropical zone of Manabí, Ecuador, was determined. Specimens were exposed at six exposure sites located at different distances from the sea. The atmosphere is classified as coastal. Chloride deposition interaction with RH–temperature complex and with wind speed show significant influence on atmospheric corrosion of low carbon steel.